Changes of the ribonuclease activity of cotyledon leaves of Linum usitatissimum irradiated by UV-B radiation and X-rays in aging - Berestyana, A.М.; Grodzinsky, D.M. (Reports of the National Academy of Sciences of Ukraine, 2014)
We investigated changes of the ribonuclease activity in ontogenesis of cotyledon leaves Linum usitatissimum irradiated by different doses of acute X-ray and UV-B radiation. The dependence of the ribonuclease activity increase on the doses and the stages of ontogeny of cotyledon leaves is found. Some hypothetical mechanisms of radiation induction of senescence are considered.